2011
DOI: 10.4034/pboci.2011.114.12
|View full text |Cite
|
Sign up to set email alerts
|

Análise Comparativa entre Aparelhos de Pressão Arterial (Digital e Aneróide) e entre Glicosímetros de Diferentes Marcas na Detecção de Pacientes Hipertensos e Diabéticos

Abstract: ), in the a preoperative dentistry situation. Methods: A sample with 60 patients was evaluated by one calibrated examiner. Blood pressure measurement was performed with both devices (aneroid and digital) with the patient at rest and the arm at the level of the heart, and then, the measurements of capillary blood glucose were performed by two glucometers (Accu-Chek Active ® and Optium™ Xceed ® ). All equipment was properly calibrated and certified by INMETRO. We applied Student's t test and analysis of the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(10 reference statements)
0
1
0
1
Order By: Relevance
“…The Optium Xceed glucose analyzer used in our study was validated via correlation with a enzymatic method (Roche Hitachi 917 System), demonstrating high correlation (r=0.938) [ 14 ] (Coyne et al, 2008). The reliability for this portable analyzer was reported as 0.962 via intra-class correlation [ 15 ] (Danieletto et al, 2011). Previous study validated the lactimeter using reference methods [ 16 ] (Fell et al, 1998) and a study from our laboratory reported a high (R=0.963) intra-class correlation between this device and the Yellow Springs lactimeter [ 17 ] (Franchini et al, 2004).…”
Section: Methods and Subjectsmentioning
confidence: 99%
“…The Optium Xceed glucose analyzer used in our study was validated via correlation with a enzymatic method (Roche Hitachi 917 System), demonstrating high correlation (r=0.938) [ 14 ] (Coyne et al, 2008). The reliability for this portable analyzer was reported as 0.962 via intra-class correlation [ 15 ] (Danieletto et al, 2011). Previous study validated the lactimeter using reference methods [ 16 ] (Fell et al, 1998) and a study from our laboratory reported a high (R=0.963) intra-class correlation between this device and the Yellow Springs lactimeter [ 17 ] (Franchini et al, 2004).…”
Section: Methods and Subjectsmentioning
confidence: 99%
“…A escolha deste método está de acordo com as orientações para monitoramento frequente da glicemia, apresenta um resultado preciso e confiável com o menor volume de amostra e menor estresse nos animais (Bock et al, 2015;Danieletto, 2011). O perfil lipídico, relativo à concentração de triglicerídeos (TRI), colesterol total (CT) e fração de lipoproteína de alta densidade (HDL), foi realizado ao final do estudo por meio de análise enzimática colorimétrica, com a utilização dos Kits de análise Labtest Diagnóstica SA (Triglicérides Liquiform -Ref.…”
Section: Perfil Glicêmico Lipídico E Risco Ateroscleróticounclassified